Clinical indications of Patoladi kwatha an experiential and scientific view - Shripathi, Acharya G; Acharya, Rajeshwari S (International Research Journal of Ayurveda & Yoga, 2021)
Kashaya formulations are commonly used in the management of both acute and chronic debilitating disorders by Ayurvedic physicians in indian subcontinent. Kashayas like Amritottara Kashaya, Maharasnadi Kashaya , Mahamanjishthadi Kashaya , Maha Sudarshana Kashaya , Triphala Kashaya , Yavadi Kwatha , Panchatikta Kashaya , Paripathadi Kashaya , Guduchi Kashaya , are few formulations which are frequently used by Ayurveda physicians . Patoladi kashaya is one such preparation which is commonly used in the management of pittaja disorders. Diseases like Amlapitt , Parinama Shoola , Annadrava Shoola , non-ulcer dyspepsia , hyperacidity syndrome , peptic ulcer , duodenal ulcer , gastric ulcer and chronic gastritis are few indications of Patoladi Kashaya . The ingredients of Patoladi Kashaya are having the actions like Pittahara, Antacid , Shoolahara, Amapachaka, Tiktarasa Yukta, anti-inflammatory , ulcer protective , soothing action on the mucous membrane and Vatahara actions. The present paper highlights about the clinical indications of Patoladi Kashaya in an experiential and scientific view.